The importance of social work as a science (The Journal of Psychology and Sociology, 2014)
In the article «The importance of social work as a science» analyzes the theories of social work. Theories identify and explore the essential, necessary connections and phenomena inherent in social processes and social development of society and the conditional nature and impact of economic, psychological, pedagogical and administrative impact on the development and behavior of social communities, groups and individuals.
Keywords: theory; pedagogical impact; administrative influence; group; identity.